ANALISIS IMPLEMENTASI PROGRAM BANTUAN TENTANG PERBAIKAN RUMAH TIDAK LAYAK HUNI DI KECAMATAN TANJUNGSARI KABUPATEN SUMEDANG - Itang Mulyana (LPPM UNSAP & FISIP UNSAP, 2018)
About the research that the author is doing is to get an overview of the implementation of the Aid Program policy on repairing Uninhabitable Homes in Tanjungsari Subdistrict, Sumedang District, weaknesses - freedom of implementation of the Aid Program about repairing Uninhabitable Homes in Tanjungsari Subdistrict, Sumedang District and trying to compensate Assistance Program on Improvement of Inadequate Houses in Tanjungsari District, Sumedang Regency. The research method used by researchers is a qualitative research method. Qualitative advice is a research procedure that produces descriptive data on words that are written or spoken from people or that are acceptable. Whereas in this research is perposive sampling technique, which is a sample retrieval technique based on needs. Implementation of RTLH Assistance Program policy in Tanjungsari Sub-District, Sumedang Regency, before all of the unfulfilled housing needs were fulfilled, activities were carried out in consultation and outreach through assistance in villages and sub-districts to get assistance, for assistance in Java Province by submitting proposals. The existence of funds in implementing the RTLH Assistance Program released from the Provincial APBD, In the implementation of the RTLH Program which is implementing the policy, namely the Village. The obstacles in implementing the RTLH Assistance Program policy in Tanjungsari Subdistrict, Sumedang Regency regarding peleksanaan are information distribution, dissemination of information is not yet evenly distributed, it is still simple and also very limited, matching policies with the environment, and lack of infrastructure advice. There have been efforts to overcome obstacles in the RTLH Policy Implementation, namely socialization to the community on a regular and continuous basis, improving the quality of communication, coordination and supervision. This method must be more varied, such as using regional TV, radio and social media.